Fuscosporellales, a New Order of Aquatic and Terrestrial Hypocreomycetidae (Sordariomycetes) - Yang J. (2017)
© 2016 Adac. Tous droits réservés. Five new dematiaceous hyphomycetes isolated from decaying wood submerged in freshwater in northern Thailand are described. Phylogenetic analyses of combined LSU, SSU and RPB2 sequence data place these hitherto unidentified taxa close to Ascotaiwania and Bactrodesmiastrum. A robust clade containing a new combination Pseudoascotaiwania persoonii, Bactrodesmiastrum species, Plagiascoma frondosum and three new species, are introduced in the new order Fuscosporellales (Hypocreomycetidae, Sordariomycetes). A sister relationship for Fuscosporellales with Conioscyphales, Pleurotheciales and Savoryellales is strongly supported by sequence data. Taxonomic novelties introduced in Fuscosporellales are four monotypic genera, viz. Fuscosporella, Mucispora, Parafuscosporella and Pseudoascotaiwania. A new taxon in its asexual morph is proposed in Ascotaiwania based on molecular data and cultural characters.